Handwritten signature verification using DRT - Vahe S. Khachaturyan (Изд-во НАН РА)
The purpose of this research is the development of mathematical and algorithmic support, which will improve the accuracy of signature verification. The algorithms compute the distances whilecomparing signatures based on DRT and HMM. For acceptance or rejection of the test signature a sliding threshold is used for all the authors, and depending on the author athresholdmethod is used, based on the distances between the test signature and the signatures of control, taking them as signs of the problem of two-class classification, using standard methods of amage classification.
Keywords: Mathematics; Algorithm